Chromosome banding in three species of Brazilian toads (Amphibia-Bufonidae) - Kasahara, S.; Silva, APZ; Haddad, CFB (Soc Brasil Genetica, 1996)
The chromosomes of Bufo crucifer, B. ictericus, and B. pamacnemis were studied by conventional staining as well as with C banding and NOR techniques. These species have a diploid number of 2n = 22 and identical karyotypes, composed of metacentric and submetacentric chromosomes. The C banding patterns and NOR data indicate that these species of Bufo are not differentiated by the distribution and amount of constitutive heterochromatin or the position of the nucleolar organizer regions.